Three-dimensional numerical analysis of fin-tube desiccant-coated heat exchanger for air dehumidification in tropics. (1st February 2023) - Liu, M.; Prabakaran, V.; Bui, T.; Cheng, G.G.; Pang, W.
Highlights: A 3-D simulation for in-depth analysis of a desiccant-coated heat exchanger. Mass and energy balances are coupled with species transports and reaction kinetics. Time-dependent and spatial distributions of reaction, temperature, and water. Parametric analysis of dehumidification performance in tropical weather conditions. Abstract: High-performance desiccant-coated heat exchangers (DCHEs) can be employed in air-conditioning systems to improve energy efficiency. While there are significant developments in experimental studies, theoretical approaches for analyzing the DCHE are impeded by the complex and coupled heat and mass transport mechanisms. Therefore, a 3D mathematical model has been developed in this work to study the dehumidification performance of a DCHE. Unlike other works reported in the literature, the developed model is able to simulate the complex coupling between heat and mass transfers in the entire volume of the heat exchanger. The model is calibrated and validated with experimental data, and a maximum discrepancy of ±8 % is recorded. A time-dependent study on the performance of the DCHE is carried out to understand the distribution of temperature, reaction rates, and water uptake in the heat exchanger. Effects of key influencing operational factors are investigated and discussed. It is indicated that the DCHE enters a stable performance state regardless of its initial adsorption state. The regeneration time should be equal to the dehumidification time to optimize the performance. A higher thermal COP is achieved under lower cooling/regeneration temperature, lower air flowrate, and shorter half-cycle time, while higher inlet air humidity ratio. Higher coated desiccant mass also provides a higher thermal COP, but this enhancement levels off once the coating grows. For DCHEs with less coating, reducing cycle time is recommended over increasing the coating amount.